Corrupção eleitoral, princípio da proporcionalidade e proteção jurídica insuficiente - Santos, Evânio José de Moura (2018)
The study of electoral fraud and the financing of electoral campaigns, grave problems that contaminate the regular dispute for elective positions, responsible for capturing the politician through economic power are the main focus of this doctoral thesis. The analysis of the phenomenon of corruption is carried out by comparing the treaties and conventions that deal with the subject, restricting the investigation to verify the applicable sanctions for the crime of electoral fraud (article 299, Electoral Code) and of the slush fund, perusing the protected legal interest and the devaluation of the criminal conduct practiced. In the context of a constitutional perspective, an analysis of the principle of proportionality and of the implicit criminal warrants is made, concluding that there is insufficient legal protection, especially with regard to the penalties applicable to the practice of said crime, existing a gap in punishability concerning the slush fund. After this confirmation, several proposals for legislative amendment (lege ferenda), imperative to combat electoral fraud, are presented, such as the urgent political reform, adequate campaign funding, typification of the slush fund and money laundering, insertion of rules of compliance within political parties, restriction of party fragmentation and appropriate criminal punishment for candidates, political leaders and voters who violate electoral criminal rules, notably because the practice of electoral fraud constitutes an attack on the Democratic State, causing numerous damages to democracy and citizenship